The mediating effect of job satisfaction on the relationship between working environment and employee performance - Nur Shifaa Athirah, Saidi (Universiti Malaysia Sarawak, 2019)
This study investigates the mediating effect of job satisfaction on the relationship between working environment and employee performance. The study aims to test a model based on five dimensions of working environment and their effect on job satisfaction and employee performance. The quantitative survey design was utilized in this study and the data were collected by using questionnaires as the research instruments. The questionnaires consist of eight sections. Actual data and pilot study were collected in same organization but in different department in Commission of Kuching North City Hall. The data were analysed by using Pearson's Correlation Analysis, Multiple Regression Analysis and Mediation Analysis. Pearson's correlation analysis was used to measure the relationship between independent variable and dependent variable, and mediator and dependent variable while multiple regression analysis were used to measure the most dominant factor between variables effected employee performance and job satisfaction. In order to test the mediator, mediation analysis was used. The determinations have proven that there is a significant relationship between independent variable and dependent variable as well as independent variable and mediator while the mediator had mediates the relationship between working environment and employeperformance.